DIASPORA AND FORMATION PROCESS OF INDONESIANESS: INTRODUCTION TO DISCUSSION - Sulistiyono, Singgih Tri (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
This Working Paper is actually a wide research plan of its effort to review Indonesianess spirit which is lately facing a hard test and challenge. The odd thing is the threat to Indonesianess continue to occur when the age of NKRI (Negara Kesatuan Republik Indonesia) becomes older and older (currently, the age is 66 years old) and the macro economy is developed more (included in G20 Countries), the world respects formal existence of any country, human rights, the information technology development becomes more sophisticated.There are sufficient reasons to prepare indications that the glue for Indonesianess becomes more fragile and experiences deterotiation process. The question may arise: awhat is the glue and adhesive material for Indonesian people and what is the function of the flue and adhesive material in formation and development process of Indonesian nation? This glue and adhesive material are very important because Indonesian nation is formed by various and different ethnic, social, religion, race which in pre-Indonesian era, they became the cause of any serious conflict. Moreover, in many cases, race and ethnic become the glue in formation process of nation. In relation to the question concerning the glue and adhesive material in Indonesian nation formation process, leaders of the first national movement quoted Ernest Renan opinion that the collective wish and hope (in order to become a nation) will become the glue and adhesive material of the nation itself. He said that a nation is a soul, aÂ  spiritualÂ  principle.Â